Epistemologi Tasawuf Hamzah Fansuri dalam Kitab Sharb Al-Ashîqîn - Ramli Cibro (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) IAIN Langsa, 2021)
The highest knowledge of the Sufis is ma'rifah which is obtained through disciplinary practice, through riyadhah and mujahada which are here referred to as Sufi epistemology. These paths are cultivated in a disciplined, methodological and objective manner so as to enable the Sufis to compile their treatises in a standard manner. As one of the most famous scholars in the archipelago, Hamzah Fansuri in the book Sharb Al-Ashiqĭn also compiled standard treatises regarding this Sufi path. Through this philosophical analysis, Hamzah Fansuri's model of Sufism epistemology is explained. The results of this study indicate that to reach the state of knowledge, a person must take spiritual steps, be under the guidance of a teacher, lead a simple life and always put their trust in Allah SWT.